The Socioeconomic Impact of Paralyzed Public Works: Analysis on the University City of the State of Amazonas - Marques Martins, Alessandro; Pantoja de Araújo, Érica; Santos Fontineles, Frank Henrique; dos Santos Santarém, Sara; Barbosa de Alencar, David; de Freitas Lopes, Gisele (International Journal for Innovation Education and Research, 2019)
The presente research refers to the analysis of the socioeconomic impacts caused by the stoppage of the University City of the State University of Amazonas in the Community Our Lady of Nazareth Lake Test with the objective of investigating the consequences of not observing the principle of efficiency in execution of the work of the University City by its managers, verifying the curret socioeconomic situation of this local population, and finally propose ways to mitigate problems and losses resulting from the stoppage, which is a matter of common interest as it covers all social classes. The research approach is quantitative because it intends to describe a phenomenon of a particular group or Society, its research instrument was the interview. To be eficiente during the execution of a work, it is necessary to have management during the process, so the Executive Branch has instituted laws fo the public Works to be managed efficiently, namely: the Growth Acceleration Program (PAC), instituted by the Decree n° 6.025/2007; the DifferentialContracting Regime (RDC), launched by Law nº 12.462/2011; and the Bidding Law, introduced by Law n° 8.666/1993. These measures sought to reduce delas and stoppages in public Works and the social and economic impacts that might be generated.